A stranger in Paris : Germany's role in republican France, 1870-1940 - Mitchell, Allan, 1933- (New York : Berghahn Books, 2006)
"In this essay, the author maintains that the French Third Republic - and European history during this period in general - can only be understood if particular attention is paid to the special relationship that existed between France and Germany. The experience of the French people was so intimately related to that of its closest neighbor that a bilateral perspective becomes unavoidable. Without the unifying theme of Germany's crucial role in acting upon and within the French Republic, this story would become a much more random tale of events. After 1870, an autonomous national history of France is no longer possible."--BOOK JACKET.
An unstable past -- An improvised state -- A voluntarist ethic -- A flagging demography -- A stagnant economy -- A sexist tradition -- An educated elite -- A xenophobic style -- A socialist revival -- A strange defeat? -- Epilogue.
Includes bibliographical references (pages 79-88) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: France -- Foreign relations -- Germany; Germany -- Foreign relations -- France; France -- Foreign relations -- 1870-1940.; Germany -- Foreign relations -- 1871-; France -- History -- Third Republic, 1870-1940.; France -- Politics and government -- 1870-1940.; France -- Relations extérieures -- Allemagne; Allemagne -- Relations extérieures -- France; France -- Relations extérieures -- 1870-1940.; Allemagne -- Relations extérieures -- 1871-; France -- Histoire -- 1870-1940 (3e République); France -- Politique et gouvernement -- 1870-1940.; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; Diplomatic relations; Politics and government; France; Germany; Öffentliche Meinung; Frankreich; Deutschland; HISTORY / Europe / France; Since 1870; Geschichte 1870-1940.; History